Type III Waardenberg Syndrome : a case report - Kuldip Garg; M. R Kamakshi (GMC Patiala Journal of Research and Medical Education, 2019)
Waardenberg syndrome is an autosomal dominant genetic disease which frequently manifests as sensorineural hearing loss, heterochromic iris, premature greying of hair. This is a case report of rare Type III waardenberg syndrome of a patient who presented to plastic surgery department of Rajindra Hospital, Patiala